A pulizziesca : genèse du roman policier corse. Issue 1 (1st January 2022) - SITBON, CLARA
Abstract : The rise of regional detective novels in Europe has generated an expanding interest, as is evident in the proliferation of scholarship on works in this genre. One type of crime narrative, however, escapes this rule: Corsican crime fiction. Because it is part of unique editorial, literary, cultural, political, and linguistic dynamics, Corsican crime fiction raises important questions about the future of regional literature within a national, international, and transnational literary canon. This article proposes a genesis of the Corsican detective novel; through a recontextualization of the genre in both the literary context of the island and the generic context of the detective novel, it will demonstrate how the serialization effect typical of crime fiction, coupled with the intrinsic plurality of the notion of authenticity, allows Corsican crime fiction to redefine the codes of the traditional detective novel and bring a new facet to the broader notion of Mediterranean Noir in its insular form known as the pulizziesca .